2009
DOI: 10.1016/j.ejpoleco.2008.11.002
|View full text |Cite
|
Sign up to set email alerts
|

As bad as it gets: Well-being deprivation of sexually exploited trafficked women

Abstract: The International Organization for Migration has collected data on trafficked individuals. The aim of this paper is to use the sub-sample of sexually exploited women in order to explore the relationship between their well being deprivation, their personal characteristics, and their working locations. We use the theoretical framework of the capability approach to conceptualize well being deprivation and we estimate a MIMIC (Multiple Indicators Multiple Causes) model. The utilized indicators measure abuse, freed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 28 publications
0
55
0
Order By: Relevance
“…Social skills are part of any sex worker's job, but, arguably, quality and quantity may be higher for escorts. Indeed, Maria Laura Di Tommaso, Isilda Shima, Steinar Strøm, and Francesca Bettio (2009), analyzing the well-being of sexually exploited trafficked women, found that fees for sexual services were strongly correlated with women's level of education. Women with high levels of education were paid 44 percent more than women with low levels of education.…”
Section: Stigmamentioning
confidence: 99%
“…Social skills are part of any sex worker's job, but, arguably, quality and quantity may be higher for escorts. Indeed, Maria Laura Di Tommaso, Isilda Shima, Steinar Strøm, and Francesca Bettio (2009), analyzing the well-being of sexually exploited trafficked women, found that fees for sexual services were strongly correlated with women's level of education. Women with high levels of education were paid 44 percent more than women with low levels of education.…”
Section: Stigmamentioning
confidence: 99%
“…The literature widely points out that the vulnerable position of women in society is a powerful push factor of human trafficking outflows (Bettio & Nandi, 2010;Clawson & Layne, 2007;Danailova-Trainor & Belser, 2006;Di Tommaso, Shima, Strøm, & Bettio, 2009). Human trafficking is apparently gender-based violence, the majority of victims being females exploited in the sex industry (UNODC, 2006;IOM, 2012).…”
Section: Vulnerabilitymentioning
confidence: 99%
“…However, the capability approach has been employed to explore questions of 'well-being deprivation of sexually exploited trafficked women' (Di Tommaso et al 2009) and has been discussed in relation to children in a range of settings including education and the street (Biggeri, Ballet and Comim 2011;Peleg 2014). The study reported here represents a significant development in the use of the capability approach as a framework for furthering understanding of children's involvement in prostitution, and how this can be understood as an issue of social justice beyond the logic of the children's rights perspective that equates sexual activity with children with sexual abuse.…”
Section: The Capability Approachmentioning
confidence: 99%